Jessica Farm - Simmons, Josh 1978- (Fantagraphics Books, 2024)
"Like a Lynchian take on Alice in Wonderland, Jessica Farm opens with an exterior of what could be any Midwestern farmhouse. Once inside, we track our titular heroine (she is a person, not a place) as she bounds out of bed on Christmas morning and goes about her routine, eventually breakfasting with her grandparents. The banality of the situation is subverted by a ratcheting sense of dread as we discover that Jessica's increasingly nightmarish house--where the inside seems bigger than the outside, like Snoopy's doghouse--is filled with creatures around every corner: some whimsical, some sexual, some despairing, and some malevolent. Most terrifying of all is Jessica's father. Will she even get to open the presents under the Christmas tree? Taking place over a single Christmas Day, Jessica Farm is a career-spanning comics project in which Simmons has been drawing one page every month for the past 24 years, starting in January 2000. This is a horror-fantasy-psychodrama that will appeal to fans of Charles Burns, David Cronenberg, and Dario Argento"--
Keywords: Simmons, Josh -- 1978-; Family violence / Comic books, strips, etc; Christmas / Comic books, strips, etc; Comic books, strips, etc / United States; Horror comic books, strips, etc; Bandes dessinées d'horreur; Christmas; Comic books, strips, etc; Family violence; Fantasy comic books, strips, etc; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; horror comics; Comics (Graphic works); Horror comics; Fantasy comics; Bandes dessinées; Comic